A contribution to the laying of foundations for dialogue between socially responsible management schools. Issue 2 (July 2017) - Rive, Jérôme; Bonnet, Marc; Parmentier, Catherine; Pelazzo-Plat, Valérie; Pignet-Fall, Lorella
Abstract: This paper presents the outcome of a research process carried out in a public school of management whose strategy from its very origin has been thoroughly focused on social responsibility. The objective was to better map out the socially responsible contribution of the school to its stakeholders in order to enable dialogue with a group of other schools of management. The starting point of the research project is the 6th principle of PRME, according to which "We will participate and support dialogue and debate among educators, students, business, government, consumer, media, civil society organisations and other interested groups and stakeholders on critical issues related to global responsibility and sustainability". Highlights: This paper presents the outcome of a research project undertaken in a state-owned school of management school, with an initial and ongoing strategy focused firmly on social responsibility. The project's objective was to produce a better map of the school's contribution to its stakeholders in terms of social responsibility and to use this as a basis for dialogue with a group of other management schools. The research project's start point is the 6th principle of PRME (Principles for Responsible Management Education), focused on dialogue. This research project was also undertaken in order to lay the foundations of a PRME chapter in French speaking countries in order to progressively create a framework for cross-fertilization among schools of management that share the same values of social responsibility.